Metabolism and antioxidant defense in the larval chironomid Tanytarsus minutipalpus: adjustments to diel variations in the extreme conditions of Lake Magadi - Lucas F. Bianchini; Chris M. Wood; Harold L. Bergman; Ora E. Johannsson; Pierre Laurent; Claudine Chevalier; Mosiany L. Kisipan; Geraldine D. Kavembe; Michael B. Papah; Kevin V. Brix; Gudrun De Boeck; John N. Maina; et al. (Biology Open, 2017)
Insect larvae are reported to be a major component of the simple but highly productive trophic web found in Lake Magadi (Kenya, Africa), which is considered to be one of the most extreme aquatic environments on Earth. Previous studies show that fish must display biochemical and physiological adjustments to thrive under the extreme conditions of the lake. However, information for invertebrates is lacking. In the present study, the occurrence of the larval chironomid Tanytarsus minutipalpus is reported in Lake Magadi for the first time. Additionally, changes in larval metabolism and antioxidant defense correlated with diel variations in the extremely hostile environmental conditions of the lake are described. Wide variations in water temperature (20.2-29.3°C) and dissolved oxygen content (3.2-18.6 mg O2 l−1) were observed at different times of day, without significant change in water pH (10.0±0.03). Temperature and dissolved oxygen were higher at 13:00 h (29.3±0.4°C and 18.6±1.0 mg O2 l−1) and 19:00 h (29.3±0.8°C and 16.2±1.6 mg O2 l−1) and lower at 01:00 h (21.1±0.1°C and 10.7±0.03 mg O2 l−1) and 07:00 h (20.2±0.4°C and 3.2±0.7 mg O2 l−1). Significant and parallel increases in parameters related to metabolism (cholinesterase, glucose, cholesterol, urea, creatinine and hemoglobin) and the antioxidant system (SOD, GPx, GR, GSH and GSSG) were observed in larvae collected at 13:00 h. In contrast, no significant changes were observed in pro-oxidants (ROS and NO), TOSC and oxidative damage parameters (LPO and DNA damage). Therefore, the observed increases in temperature and dissolved O2 content in Lake Magadi were associated with changes in the antioxidant system of T. minutipalpus larvae. Adjustments performed by the chironomid larvae were efficient in maintaining body homeostasis, as well as protecting biomolecules against oxidative damage, so that oxidative stress did not occur. GSH-GSSG and GPx-GR systems appeared to play an essential role in the adjustments displayed by the chironomid larvae during the diel changes in the extreme conditions of Lake Magadi.